“Keeping us strong”: Negotiating power, literacies and learning in an Aboriginal context - Smith, Melanie Sarah (Curtin University, 2013)
This thesis is an ethnographic study of literacy and learning practices at a remote Aboriginal adult education centre in Western Australia. Drawing on theories of literacy as social practice, this research describes and analyses what happens in adult Aboriginal education at the level of practice: in particular, how one learning community negotiates engagement with education while ensuring that their personal autonomy, and the everyday contexts of their lives, are not compromised as a result.